Hair-thread tourniquet syndrome: Two case reports and review of the literature - Nuh Evin; Joshgun Gasimov; Fatih Osman Demir; Yusuf Erbayat (Turkish Journal of Plastic Surgery, 2024)
Hair-thread tourniquet syndrome (HTTS) is an emergency phenomenon in which hair or thread tightly wraps around a protruding appendage of the body, resulting in pain, swelling, and rarely ischemia and amputation. While the toes, fingers, and external genitalia are the most affected areas, it can also impact other protruding parts of the body. Nevertheless, except for a few cases of skin tags and hemangioma, HTTS associated with a protruding skin mass is extremely rare in the literature. In this study, we present the management of two cases: One involving a pediatric patient with HTTS affecting the right fourth toe and the other involving a protruding pyogenic granuloma on the back of an adult patient.